Clinical Presentation of Chronic Traumatic Encephalopathy - Mariani, Megan; Alosco, Michael L.; Mez, Jesse; Stern, Robert A. (Seminars in Neurology, 2020)
Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease associated with repetitive head impacts (RHI), such as those received in contact/collision sports, blast injury in military veterans, and domestic violence. Currently, CTE can only be diagnosed following death. Although the clinical features of former boxers have been described for almost a century, and there is increasing evidence of long-term cognitive and neuropsychiatric impairments in living former American football players, the specific clinical presentation associated with underlying CTE neuropathology remains unclear. These features include diverse and nonspecific changes in cognition, mood, behavior, and motor functioning. Currently, there are no validated and widely accepted clinical diagnostic criteria. Proposed criteria are primarily based on retrospective telephonic interviews with the next of kin of individuals who were diagnosed with CTE postmortem. Prospective studies involving individuals presumably at high risk for CTE are underway; these will hopefully clarify the clinical features and course of CTE, allow the diagnostic criteria to be refined, and lead to the development and validation of in vivo biomarkers. This article reviews what is currently known about the clinical presentation of CTE and describes the evolution of this knowledge from early case reports of “punch drunk” boxers through larger case series of neuropathologically confirmed CTE. This article concludes with a discussion of gaps in research and future directions to address these areas.
Keywords: chronic traumatic encephalopathy; neurodegenerative disease; tauopathy; traumatic encephalopathy syndrome; repetitive head impacts; football players; biomarkers